PENGEMBANGAN MEDIA CERITA TOKOH HURUF BERGAMBAR PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS I SD YPK 10 IMANUEL KEBAR - Agustina Feti Suryanti; Siti Fatimatul Zahra; Ainul Yaqimah; Siti Muflihah; Monica Wahyu Pertiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT This study aims to determine 1) the description of the needs of first-grade students of YPK 10 Imanuel Kebar Elementary School regarding mastery of illustrated letter character stories. 2) prototype of illustrated letter character stories in letter recognition. 3) validity and practicality of illustrated letter character stories. This research is a development using the research stages of Borg & Gall. The data collection technique used is by interviewing and filling out questionnaires. The research method on the development of letter character story media is carried out using the